The Influence of Job Satisfaction, Workload, and Organizational Commitment on Turnover Intention Mediated by Emotional Exhaustion (Empirical Study: Employees of PT XYZ in Bekasi) - Situmorang, Indra Bakti; Heryjanto, Andreas (Journal of Management, 2024)
The purpose of this study is to look at the impact of job satisfaction, workload, and organizational commitment on turnover intention, which is mediated by emotional tiredness in PT staff. XYZ is in Bekasi. This study's data was gathered using an online survey of PT XYZ workers using Google Forms. There will be 137 respondents in this study, which employs a correlational quantitative technique and is processed using the PLS version 4 software. The study's findings show that work satisfaction has no substantial influence on turnover intentions. Other results prove that workload has no significant effect on turnover intention, organizational commitment has no significant effect on turnover intention, emotional exhaustion has a significant positive effect on turnover intention, job satisfaction has a significant negative effect on turnover intention that is mediated by emotional exhaustion, workload has a significant positive effect on turnover intention that is mediated by emotional exhaustion, organizational Theoretically, the implications of this research are to provide benefits in the form of knowledge to academics, practitioners, and regulators, whereas managerially, management must encourage open communication between employees and management so that employees can communicate the problems they face in the workplace more comfortably.